Do specific metacognitive training modules lead to specific cognitive changes among patients diagnosed with schizophrenia? A single module effectiveness pilot study. Issue 3 (3rd July 2017) - Kowalski, Joachim; Pankowski, Daniel; Lew-Starowicz, Michał; Gawęda, Łukasz
Abstract: Background and objectives: This study aimed to assess specific changes in cognitive biases and the efficacy of two individual metacognitive training (MCT) modules which target the jumping to conclusions bias and theory of mind deficits among people diagnosed with schizophrenia spectrum disorders. Methods: Thirty-one patients were randomly allocated to three groups: jumping to conclusions, theory of mind, and a control group. Paranoid ideation, jumping to conclusions, and theory of mind were assessed pre- and post-treatment. Results: There were no significant changes in paranoid ideation pre- and post-intervention in any group. There was a tendency towards a decrease in the jumping to conclusions bias in the corresponding group in comparison to the other two groups. There was a significant change in the theory of mind deficit in the corresponding group in comparison to the jumping to conclusions group, but not the control group. Conclusions: Our study tentatively suggests that a single module of MCT training based on theory of mind and jumping to conclusions may affect specific cognitive biases.